2019
DOI: 10.1002/polb.24829
|View full text |Cite
|
Sign up to set email alerts
|

Morphology diagram of PE gel films in wide range temperature‐strain space: An in situ SAXS and WAXS study

Abstract: Deformation-induced structural evolution of polyethylene (PE) gel films were investigated by in situ synchrotron radiation SAXS and WAXS techniques during stretching at temperatures from 25 C to 110 C. The structural evolutions along tensile strains showed distinct behaviors in the four temperature regions divided by T αI and T αII given by DMA and the onset point of melting measured by DSC, respectively, which was determined by the coupling effects of external stretching field and temperature. Finally, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…SAXS measurements have been performed to assess exclusion behaviors with the help of long periods of PVDF and PBSU. [ 28,29 ] As discussed in our previous work, [ 19 ] the scattering peaks of neat PVDF and PBSU locate at q = 0.53 and 0.74 nm −1 , respectively. In each Lorentz‐corrected SAXS profile of the blend specimens (Figure 2c), there is only one peak locating at q = 0.28 nm −1 (200–141) and 0.35 nm −1 (240–141), corresponding to the long periods of 22.4 nm and 17.9 nm, respectively.…”
Section: Resultsmentioning
confidence: 84%
“…SAXS measurements have been performed to assess exclusion behaviors with the help of long periods of PVDF and PBSU. [ 28,29 ] As discussed in our previous work, [ 19 ] the scattering peaks of neat PVDF and PBSU locate at q = 0.53 and 0.74 nm −1 , respectively. In each Lorentz‐corrected SAXS profile of the blend specimens (Figure 2c), there is only one peak locating at q = 0.28 nm −1 (200–141) and 0.35 nm −1 (240–141), corresponding to the long periods of 22.4 nm and 17.9 nm, respectively.…”
Section: Resultsmentioning
confidence: 84%
“…The small peak that appears during the long-period decreasing stage of UHMWPE-180 is not the true long period because most of the lamellar crystals are already tilted or broken and gradually rotate away from the stretching direction. It was also found that the rotation of the crystals resulted in the inability to calculate the true long period during the stretching of the PE gel film . In the middle stages of hot stretching, for UHMWPE-135 and UHMWPE-138, the long period slightly decreases, and the distribution of long periods gradually decreases, indicating that both the formation of the prereserved shish-induced shish-kebab crystals and that of the stretch-induced shish-kebab crystals gradually reach a constant.…”
Section: Results and Discussionmentioning
confidence: 99%
“…PM crystallizes in an orthorhombic unit cell with parameters a = 0.742 nm, b = 0.495 nm, c = 0.255 nm, and β = 90 • , with a P-D 2h space group [63,64]. The crystallographic planes for these peaks are (110) and (200), respectively [65,66].…”
Section: How the Cooling Rate Affects The Crystallization Of The Pvdf Phase In Block Copolymers And Blendsmentioning
confidence: 99%